Actualidade Económica de Moçambique: Transitando para um crescimento mais inclusivo (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique Economic Update: Shifting to More Inclusive Growth (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique rising: building a new tomorrow - Ross, Doris C. (International Monetary Fund, African Department, 2014)
This publication highlights Mozambique's remarkably strong growth over the two decades since the end of the civil war in 1992, as well as the major challenges that remain for the country to rise out of poverty and further its economic development. Chapters explore such topics as the role of megaprojects and their relationship to jobs and growth; infrastructure and public investment; Mozambique's quest for inclusive growth; developing the agricultural sector; and building a social protection floor
OCLC: ocn879526832
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; Social Protection PEA; agriculture / agricultura; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; infrastructure / infrastrutura; social protection / proteção social